Availability, affordability and price components of insulin products in different-level hospital pharmacies: Evidence from two cross-sectional surveys in Nanjing, China. - Lulu Wang (Public Library of Science (PLoS), 2021)
The essential medicine--insulin cannot be easily accessed and afforded in many countries. To help address this issue, we evaluated the availability, affordability and price of insulin products in Nanjing, eastern China. Two cross-sectional studies were conducted in 2016 and 2018. A total of 56 hospital pharmacies were sampled, using a simplified and adapted World Health Organization/Health Action International (WHO/HAI) methodology. Prices were expressed as Median Price Ratios (MPRs) to Australian Pharmaceutical Benefit Scheme (PBS) prices. In addition, we investigated the price components of seven selected insulin products as a case study before and after the Online Centralized Procurement Policy for Hospital Drugs in May, 2018. Affordability was presented as the number of daily wages of the lowest paid unskilled government worker (LPGW) required to purchase 1000IU of insulin based on the average courses of treatment, approximately 30 days' treatment. The availability of insulin products was very high in secondary hospitals and tertiary hospitals both in 2016 and 2018, but in community hospitals was very low. In 2018, the availability of prandial insulin products showed fluctuation compared to 2016. The availability of pre-mixed human insulin products was over 95% overall, and also very high (80%) in community hospitals in 2018. The prices of insulin products were much lower than PBS prices of Australian in this study, with the MPRs less than 1 (0.32 to 0.71 in 2016 vs. 0.30 to 0.68 in 2018) for all insulin types. But insulin products in Nanjing in 2016 and 2018 were considered unaffordable, because the number of daily wages of the LPGW needed to purchase for the 30 days treatment of insulin products ranged from 2.26 to 8.49 in 2016 and 1.88 to 7.09 in 2018. The manufacturers' selling price contributed the main part (74.15% to 77.70% before and 74.86% to 91.51% after the implementation of the bidding policy) of the price components of target insulin brands. The availability of insulin products was high in secondary hospitals and tertiary hospitals, but lower in community hospitals. However, the affordability in community hospitals was better than other hospitals, but the insulin products were still unaffordable for patients on low incomes. Further improvements of the availability accessibility and affordability of medicines in advancing health insurance policies and lowering drug prices should be put forward.